Konsep Pendidikan Karakter Dalam Al-Qur'an Dan Hadits - Mardiah Mardiah; Martina Napratilora (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
The formulation of the problem in this writing is how the concept of character education according to the Qur'an and Hadith? While the goal is to know the concept of character education that exists in the Qur'an and Hadith. This type of research is library research, the data sources used are primary and secondary data sources with deductive and inductive thinking. How to collect data with documentation study and analyze with the method of Tafsir maudhu'i and sarah Hadith. The results found in the verses of the Qur'an about the concept of character education are found in surah as-Shaff verses 2-3, surah Lukman verses 12-14 and surah at-Taubah verse 119. While the Hadith related to the concept of character education is Hadith about hypocrisy, Hadith devotion to both parents and Hadith about honesty, the three Hadiths are narrated by Muttafaqun 'alaih. The concept of character education according to the verses of the Qur'an above we must be istiqomah and unity between words and deeds, be grateful to Allah SWT, believe in Allah SWT by not associating with Him, devotion to parents, honest, avoid hypocritical traits to himself and others, while the concept of character education according to the Hadith we must not lie, betray, do not keep promises, but we must respect, love and be honest to anyone whose goal is to make a perfect human being.